Effect of generalized joint hypermobility on knee function and muscle activation in children and adults. Issue 5 (30th August 2013) - Jensen, Bente R.; Olesen, Annesofie T.; Pedersen, Mogens T.; Kristensen, Jens H.; Remvig, Lars; Simonsen, Erik B.; Juul‐Kristensen, Birgit
ABSTRACT Introduction: We investigated muscle activation strategy and performance of knee extensor and flexor muscles in children and adults with generalized joint hypermobility (GJH) and compared them with controls. Methods: Muscle activation, torque steadiness, electromechanical delay, and muscle strength were evaluated in 39 children and 36 adults during isometric knee extension and flexion. Subjects performed isometric maximum contractions, submaximal contractions at 25% maximum voluntary contraction (MVC), and explosive contractions. Results: Agonist activation was reduced, and coactivation ratio was greater in GJH during knee flexion compared with controls. Torque steadiness was impaired in adults with GJH during knee flexion. No effect of GJH was found on muscle strength or electromechanical delay. Correlation analysis revealed an association between GJH severity and function in adults. Conclusions: The results indicate that muscle activation strategy and quality of force control were significantly affected in adults with GJH during knee flexion, whereas only muscle activation strategy was affected in children with GJH. Muscle Nerve 48:762–769, 2013